Taxonomy and distribution of Tapinoma ants (Formicidae: Dolichoderinae) in Colombia. (2018)
The species of the genus Tapinoma are reviewed for the first time in Colombia. Four species are recognized, T. litorale, T. melanocephalum and T. ramulorum are recorded and described, as well one undescribed species. A taxonomic key based on the workers, images and distribution maps are provided.